Helping South Asia Cope with Natural Disasters : The Role of Social Protection - World Bank (Washington, DC, 2014)
Addressing the social protection needs of households during emergencies is a major development issue. Without social protection measures, such as cash transfers for basic needs or workfare programs, many households faced with large economic and natural shocks might deplete their human and physical capital, reducing their ability to participate in economic development. Social protection measures (cash transfers, in particular) are therefore assuming a growing role in the World Bank to help the poor cope with the aftermath of a disaster. In South Asia, all three recent major emergency-related operations in South Asia (Sri Lanka, Maldives, and Pakistan) included cash transfers components. This discussion paper, an input to the South Asia region's social protection and hazard risk management strategies, describes the cash transfer instruments supported by the Bank in South Asia, evaluates their design and implementation, and suggests improvements to increase their effectiveness. Based on available evidence, the paper finds that cash transfers appear to have performed well in providing relief to affected households, suggesting that they should remain an integral part of Bank-financed support for natural disasters. The paper also suggests that the Bank can ensure timely and high-quality support through a best-practice design toolkit, a right-on-time technical assistance facility, and by integrating social protection in emergency preparedness by building the capacity of national social assistance (cash transfers) agencies to respond to natural disasters. Although the focus is on cash transfers, the note also discusses other types of social protection mechanisms used in emergencies in South Asia and worldwide, e.g., workfare or social care for the vulnerable, and which might also appropriate for including in Bank emergency operations. The note covers South Asia, but lessons from this region may also be relevant for governments of other developing countries and donors. Finally, while the focus of the paper is on social protection instruments for natural disasters, several of these instruments have also proved useful in post-conflict situations and in economic crises.